Homeostasis - Hayward, Nick; Collins, Cath; Wilson, Elle; Bertsa, Elenora (Films for the Humanties & Sciences, 2009)
In this program we'll explore the concept of homeostasis. We'll ask what homeostasis is, why it is important, take a look at detecting changes from the stable state, counteracting changes from the stable state, and how homeostasis works.